CHARACTERIZATION OF SELF-ASSEMBLED PROTEIN THIN FILM ON FLAT AND NON-FLAT SUBSTRATE - ASSIS, ODILIO B. G.; BERNARDES FILHO, RUBENS (Revista Brasileira de Engenharia de Biossistemas, 2008)
In this study we have characterized the surfaces of lysozyme globular protein films self-assembled on glassy substrate. Flat slides and cylindrical glass fibers were used as solid supports for protein (concentration 10-4 M) immobilization and the surfaces scanned with atomic force microscopy (AFM) along the deposition time. AFM data allowed following the surface roughness reduction as the film was formed. The deposition features were quite similar for both substrates, whereas on the flat surface a more regular deposition was observed. The thickness of grafted layers was determined from differences between deposited and non-deposited regions and measured, after 10 min immersion, as 7.6 ± 1.4 for flat and 10.4 ± 2.6 nm for cylindrical surface, suggesting by comparison with the protein molecule dimensions, that the adsorption should be a multilayer process under the experimental conditions used in this work.